Effect of Bodyweight Squat Exercise With Blood Flow Restriction on Sprint and Jump Performance in Collegiate Soccer Players - Okan Kamiş; Hadi Nobarı; Christopher Macdonald; Robert Blaisdell; Muhammet Kurt (Pamukkale Spor Bilimleri Dergisi)
This study investigated the effect of bodyweight squat (BWS) with blood flow restriction (BFR) exercise on sprint and jump performance in collegiate male soccer players. Twenty-four male collegiate soccer players (age: 19.3±1.0 years; height: 178.8±5.8 cm; body mass: 73.5±10.7 kg) were randomly divided equally into BFR or control groups. The BFR group performed BWS with BFR, while the Control group performed BWS without BFR 3x/week for eight weeks on nonconsecutive days. Both groups performed BWS for 30-15-15-15 repetitions with 30-second rest between sets (with continuous BFR pressure between sets). Limb occlusion pressure (LOP) was measured in a supine position after 10 min of passive rest by the automated device. Progressive overload was achieved by increasing LOP % weekly. The pressure was set at 60% LOP for the first four weeks and then was increased to 70% LOP for weeks 5 and 6 and then to 80% LOP for weeks 7 and 8. Countermovement jump (CMJ) and 30m sprint performance were assessed before and after the exercise program. No statistically significant differences between groups were identified. Both groups significantly increased sprint and CMJ performance (p